Jaringan Akuntan Manajemen, Akuntansi Manajemen Strategis, Budaya Organisasi dan Kinerja Organisasi - Maryati, Sri; Listya, Anisa; Igamo, Alghifahri Mahdi (E-Jurnal Akuntansi; Vol 33 No 8 (2023), 2023)
This research aims to empirically test strategic management accounting practices by involving the role of management accountant networks and the moderation of organizational culture and their implications for company performance. The data was obtained using a survey method, namely practitioners who act as management accountants for small businesses in South Sumatra. The research data was processed and analyzed using SEM-PLS. The results show that the relationship between the management accountant network and strategic management accounting, organizational culture moderates the relationship between the management accountant network and strategic management accountants. Strategic management accountants mediate the relationship between management accountant networks and organizational performance. The Importance of the Role of a good network of management accountants among small business actors in South Sumatra by understanding the concept of strategic management.  Keywords: Management Accountant; Strategic Management Accounting; Organizational Performance.